ANALISIS KEKUATAN OTOT TUNGKAI DAN KEMAMPUAN LOMPAT RAIHAN PADA SMASH ATLET BOLAVOLI PUTRA UNIT KEGIATAN MAHASISWA UNIVERSITAS NEGERI SURABAYA - Wiranda, Bima Mitra (Jurnal Kesehatan Olahraga, 2019)
In the motion required smash repulsion of leg muscle, where it is needed to maximize the high jump as well as improve the achievement of the arm to hit the ball over the net. The larger the leg muscle strength possessed the greater the repulsion generated so that the movement could smash easily direct the ball into the corner diingankan The aim of this study was to determine the level of Limbs Muscle Strength and Capabilities Jump Smash Athlete Achievement In volleyball Men's Student Activity Unit Surabaya State University. This target research is 12 men volleyball athlete?s Unit Kegiatan Mahasiswa State University of Surabaya. Research conducted at Gelanggang Pumuda the State University of Surabaya. The research instrument used in this study is Limbs Muscle Strength Test (Leg Dynamometer) to measure the strength of leg muscles, and Sargent Jump Test to measure the achievement of high range with a vertical jump. The results of the series of tests showed that the average Limb Muscle Strength for 167.75 kg into the category of Being, and the average test Sargent Jump for 59.17 cm in the category Good. The conclusion of this study is that in addition to training the upper extremity on volleyball smash, it can be said that lower extremity training should not be ignored because in fact the body in the lower extremity is a support for the whole body also plays a role when making leaps.         Keywords : leg muscle strength, Ability reach jump, smash volleyball